MicroRNA-mediated regulation of ferroptosis via GPX4: mechanisms and therapeutic opportunities - S Satvika; B Nivedhitha; K Mounish; B Prathamesh; K L Milan; K. M. Ramkumar (Molecular Biology Reports, 2026)

Source, dynamic, and environmental impact of microplastic in aquatic ecosystem: A review - N. Radha; G. Sreelal; Sakthivel Murugan; S. Ramkumar; Balamurugan Paneerselvam (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Photocatalytic and antifouling performance of g-C3N4, CeO2, and ZnO-grafted PVDF/TiO2 nanohybrid membranes: a comparative study - S. Nivedita; M. Induja; Mani Durai; Karthikeyan Manivannan; Vinoth Kumar Raja; Nagaraj Murugan; Dharani Shanmugapriya; Vijayakumar Paranthaman; Amanullah Fatehmulla; Ramkumar Vanaraj; Paskalis Sahaya Murphin Kumar (Environmental Geochemistry and Health, 2026)

Modulating IL-1β-induced pro-atherogenic endothelial responses through drug repurposing - Kundan Solanki; Sk Rameej Raja; Sunanda Samanta; P. S. Shishira; Anjali Roy; Parimal Kar; Swati Biswas; K. M. Ramkumar; Mirza S. Baig (Inflammopharmacology, 2026)

Tectono-climatic controls on episodic paleosurface development in the Cauvery Basin, Southern India: Implications for basin-scale landscape dynamics - AL Fathima; M. Ramkumar; K. Balasubramani; P.D. Roy; Pankaj Kumar; R. Nagarajan; S. Rajveer (Rhizosphere, 2026)

Spatiotemporal patterns of jellyfish distribution along the Maharashtra coast, India - M.R. Ashpel Mano; S. Ramkumar; Asha T. Landge; S. Abuthagir Iburahim; K. Nikhil; Sonam Angmo; Karankumar Ramteke; B.B. Nayak; Suryapraba (Regional Studies in Marine Science, 2026)

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Acaricide resistance and possible underlying biochemical mechanisms in the two-spotted spider mite, Tetranychus urticae Koch, on cut flowers - Sundaravadivel Sathiya Priya; Ettiappan Sumathi; Ramkumar Haran; Perumal Renukadevi; Marimuthu Murugan; Thirumalaiandi Ramasubramanian; K. K Kumar; S. P Thamarai Selvi; Sivakumar Kowsika (Ecotoxicology, 2025)

Unveiling microplastic contamination in seafood: Source, fate, analytical methods, health impacts, mitigation strategies and scientometric trends - Ulaganathan Arisekar; E. Arivukumar; Abuthagir Iburahim; Rajendran Shalini; Balasubramanian Sivaraman; Manickam Selvaraj; Hamed A. Ghramh; Bhagyalakshmi Kalidass; Vijayakumar Renuka; S. Ramkumar (Marine Pollution Bulletin, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Synthesis and characterization of lanthanum-assisted aluminium metal-organic frameworks for the removal of fluoride ions from an aqueous environment - S. Anu Ratthika; K. Ramkumar; S.SD. Elanchezhiyan; Rajesh Kumar; S. Meenakshi (Journal of Environmental Chemical Engineering, 2025)

Application of quality by design in optimization of nanoformulations: Principle, perspectives and practices - Devendra Birla; Nikhil Khandale; Bushra Bashir; Md. ShahbazAlam; Sukriti Vishwas; Gaurav Gupta; Harish Dureja; Popat S. Kumbhar; John Disouza; Vandana Patravale; Francisco Veiga; Ana Cláudia Paiva-Santos; et al. (Drug Delivery and Translational Research, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Correction: Exploration of bioactive molecules from Sesbania grandiflora (L.): identification of squalene as an effective compound against the two-spotted spider mite, Tetranychus urticae Koch, through molecular docking - S. S. Praveen Joshi; Ettiappan Sumathi; Marimuthu Murugan; Ramkumar Haran; Sundaravadivel Sathiya Priya; Ganeshan Shandeep; Subbarayalu Mohankumar; Doraiswamy Uma; Ashitha Nelson (Experimental and Applied Acarology, 2025)

Exploration of bioactive molecules from Sesbania grandiflora (L.): identification of squalene as an effective compound against the two-spotted spider mite, Tetranychus urticae Koch, through molecular docking - S. S. Praveen Joshi; Ettiappan Sumathi; Marimuthu Murugan; Ramkumar Haran; Sundaravadivel Sathiya Priya; Ganeshan Shandeep; Subbarayalu Mohankumar; Doraiswamy Uma; Ashitha Nelson (Experimental and Applied Acarology, 2025)

Symbiosis in Sea Anemones: A Few Case Reports Along the Bay of Bengal Large Marine Ecosystem - L. Ranjith; R. Saravanan; S. Ramkumar; C. Kalidas; R. Vinothkumar; D. Linga Prabu; M. Kavitha; A. Mathan Babu; R. Kalaibharathi; P. S. Asha (Marine Ecology, 2025)
The most well‐known relationship is between sea anemones and decapod crustaceans, of which crabs are classic examples of mutualistic interactions in which both organisms benefit from living with zooxanthellae and hermatypic or reef‐forming corals. A marine ecology study off the southern coast of Tamil Nadu revealed five types of sea anemones that cohabit symbiotically with other marine animals. These species include Stichodactyla haddoni (Saville‐Kent, 1893), Entacmaea quadricolor (Leuckart in Ruppell and Leukart, 1828), Radianthus (= Heteractis ) magnifica (Quoy and Gaimard, 1833), Radianthus (= Heteractis ) crispa (Ehrenberg, 1834), and Calliactis polypus (Forsskal, 1775), are found in symbiotic associations. This observation revealed that the decapod porcelain crab Neopetrolisthes is associated with the sea anemones Radianthus and Entacmaea , whereas this has not been reported in Stichodactyla . The hermit crab anemone, C. polypus , is generally associated with hermit crabs, and we report this association for the first time in live gastropod, Turbinella pyrum (Linnaeus, 1767). A few animals (both the host and symbiont) were brought to the cnidarian laboratory at the ICAR‐Tuticorin Regional Station of the CMFRI, where they were maintained in optimum seawater for further observations. The present study aimed to compare previous reports of symbiosis in decapod crustaceans and gastropods with sea anemones from Indian waters to provide insight into the dynamics of symbiosis in the Bay of Bengal Large Marine Ecosystem.

Effect of Bis (methyl glycol) phthalate on endoplasmic reticulum stress in endothelial cells - Verma Nishitha-Hiresha; Raghavan Varsha; S. Srinidhi; Ravichandran Jayasuriya; Kannan Harithpriya; Paromita Chakraborty; Kunka Mohanram Ramkumar (Environmental Toxicology and Pharmacology, 2024)

Biomonitoring of mercury and selenium in commercially important shellfish: Distribution pattern, health benefit assessment and consumption advisories - Ulaganathan Arisekar; Rajendran Shalini; Soundar Abuthagir Iburahim; S. Deepika; C. Prabhanjan Kumar Reddy; Kanagaraja Anantharaja; Mohammed F. Albeshr; Sugumar Ramkumar; Bhagyalakshmi Kalidass; K. Tamilarasan; N. Nandha Kumar (Environmental Geochemistry and Health, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

A comprehensive review of beetroot ( Beta vulgaris L.) bioactive components in the food and pharmaceutical industries - Muthu Thiruvengadam; Ill-Min Chung; Ramkumar Samynathan; S. R. Harish Chandar; Baskar Venkidasamy; Tanmay Sarkar; Maksim Rebezov; Olga Gorelik; Mohammad Ali Shariati; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Ensemble classifier fostered detection of arrhythmia using ECG data - M. Ramkumar; Manjunathan Alagarsamy; A. Balakumar; S. Pradeep (Medical & Biological Engineering & Computing, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Biorecognition elements appended gold nanoparticle biosensors for the detection of food-borne pathogens - A review - Sandhya Sadanandan; Meenakshi V. S; Keerthana Ramkumar; Neeraja P. Pillai; Anuvinda P; Sreelekshmi P. J; Devika V; Ramanunni K; Jeevan Sankar R; M.M. Sreejaya (Food Control, 2023)

Pigment composition analysis of fruit pulp in the recombinant progenies reveals the polygenic nature of pulp color inheritance in guava (Psidium guajava L.) - Madhubala Thakre; Hanamant S.; Ramkumar M.K.; Rutuparna Senapati; Shalini Gaur Rudra; Supradip Saha; A. Nagaraja; M. K. Verma; Gopala Krishnan S.; Eldho Varghese; Amitha Mithra Sevanthi (Tree Genetics & Genomes, 2023)

Ureaplasma parvum infection induces inflammatory changes in vaginal epithelial cells independent of sialidase - Emmanuel Amabebe; Lauren S. Richardson; Giovana Fernanda Cosi Bento; Enkhtuya Radnaa; Talar Kechichian; Ramkumar Menon; Dilly O. C. Anumba (Molecular Biology Reports, 2023)

Sustainable approach to manage the vulnerable rodents using eco-friendly green rodenticides formulation through nanotechnology principles – A review - S. Karthick Raja Namasivayam; Subramanian Srinivasan; Krishnappa Samrat; Bala Priyalakshmi; Ramkumar Dinesh Kumar; Arvind Bharani; Ramkumar Ganesh Kumar; M. Kavisri; Meivelu Moovendhan (Process Safety and Environmental Protection, 2023)

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

Genetic diversity analysis of wild and cultivated Rosa species of India using microsatellite markers and their comparison with morphology based diversity - Abhay Kumar Gaurav; Namita; D. V. S. Raju; M. K. Ramkumar; M. K. Singh; Bhupinder Singh; S. Gopala Krishnan; Sapna Panwar; Amitha Mithra Sevanthi (Journal of Plant Biochemistry and Biotechnology, 2022)

Sharpening gene editing toolbox in Arabidopsis for plants - Sagar S. Arya; Binod K. Mahto; Thakku R. Ramkumar; Sangram K. Lenka (Journal of Plant Biochemistry and Biotechnology, 2020)

Novel pathways of inflammation in human fetal membranes associated with preterm birth and preterm pre-labor rupture of the membranes - Ramkumar Menon; Faranak Behnia; Jossimara Polettini; Lauren S. Richardson (Seminars in Immunopathology, 2020)

Cross-sectional study on rotavirus A (RVA) infection and assessment of risk factors in pre- and post-weaning piglets in India - O. R. VinodhKumar; S. Sircar; B. S. Pruthvishree; K. R. Nirupama; B. R. Singh; D. K. Sinha; Ramkumar Rupner; A. Karthikeyan; R. Karthikeyan; Z. B. Dubal; Y. S. Malik (Tropical Animal Health and Production, 2020)

Smartphone geospatial apps for dengue control, prevention, prediction, and education: MOSapp, DISapp, and the mosquito perception index (MPI) - A. N. Babu; E. Niehaus; S. Shah; C. Unnithan; P. S. Ramkumar; J. Shah; V. V. Binoy; B. Soman; M. C. Arunan; C. P. Jose (Environmental Monitoring and Assessment, 2019)

Morphological Deformities in Neotrygon kuhlii (Muller & Henle, 1841) from Gulf of Mannar, Bay of Bengal, India - L. Ranjith; R. Saravanan; C. Kalidas; M. Kavitha; S. Ramkumar; K. K. Joshi; P. P. Manojkumar (Thalassas: An International Journal of Marine Sciences, 2019)

Identification of saline water intrusion in part of Cauvery deltaic region, Tamil Nadu, Southern India: using GIS and VES methods - G. Gnanachandrasamy; T. Ramkumar; S. Venkatramanan; S. Y. Chung; S. Vasudevan (Marine Geophysical Research, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Influence of physicochemical and nutritional factors on bacterial diversity in mangrove sediments along the southwest coast of Tamilnadu, India - S. Prakash; R. Ramasubburayan; P. Iyapparaj; N. K. Ahila; V. Sri Ramkumar; A. Palavesam; G. Immanuel; E. Kannapiran (Environmental Monitoring and Assessment, 2015)

Environmental monitoring and assessment of heavy metals in surface sediments at Coleroon River Estuary in Tamil Nadu, India - S. Venkatramanan; S. Y. Chung; T. Ramkumar; S. Selvam (Environmental Monitoring and Assessment, 2015)

Comprehensive studies of hydrogeochemical processes and quality status of groundwater with tools of cluster, grouping analysis, and fuzzy set method using GIS platform: a case study of Dalcheon in Ulsan City, Korea - S. Venkatramanan; S. Y. Chung; R. Rajesh; S. Y. Lee; T. Ramkumar; M. V. Prasanna (Environmental Science and Pollution Research, 2015)

Influence of hydrogeochemical processes and assessment of suitability for groundwater uses in Busan City, Korea - S. Y. Chung; S. Venkatramanan; T. H. Kim; D. S. Kim; T. Ramkumar (Environment, Development and Sustainability, 2015)

Nucleotide variation and identification of novel blast resistance alleles of Pib by allele mining strategy - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; M. S. Prasad; V. Ravindra Babu (Physiology and Molecular Biology of Plants, 2015)

An assessment of selected hydrochemical parameter trend of the Nakdong River water in South Korea, using time series analyses and PCA - S. Y. Chung; S. Venkatramanan; N. Park; R. Rajesh; T. Ramkumar; B. W. Kim (Environmental Monitoring and Assessment, 2015)

Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach - S Veerasingam; R Venkatachalapathy; N Basavaiah; T Ramkumar; S Venkatramanan; K Deenadayalan (Journal of Earth System Science, 2014)

Heavy metal distribution in surface sediments of the Tirumalairajan river estuary and the surrounding coastal area, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; S. Vasudevan (Arabian Journal of Geosciences, 2014)

Speciation of selected heavy metals geochemistry in surface sediments from Tirumalairajan river estuary, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; M. P. Jonathan (Environmental Monitoring and Assessment, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

The molecular diversity and evolution of Rice tungro bacilliform virus from Indian perspective - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; B. Sailaja; Jagrati Singh; G. Ramkumar; D. Krishnaveni; S. M. Balachandran (Virus Genes, 2012)

Genetic variation of coat protein gene among the isolates of Rice tungro spherical virus from tungro-endemic states of the India - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; G. Ramkumar; D. Krishnaveni; C. N. Neeraja; M. Sheshu Madhav; D. Ladhalakshmi; S. M. Balachandran; B. C. Viraktamath (Virus Genes, 2012)

Persistence and Dissipation Kinetics of Deltamethrin on Chili in Different Agro-Climatic Zones of India - Suneet Pandher; S. K. Sahoo; R. S. Battu; Balwinder Singh; M. S. Saiyad; A. R. Patel; P. G. Shah; C. Narendra Reddy; D. Jagdishwar Reddy; K. Narasimha Reddy; Ch. Sreenivasa Rao; Tirthankar Banerjee; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Environmental magnetic and geochemical characteristics of Chennai coastal sediments, Bay of Bengal, India - R VENKATACHALAPATHY; S VEERASINGAM; N BASAVAIAH; T RAMKUMAR; K DEENADAYALAN (Journal of Earth System Science, 2011)

Alterations in inheritance pattern and level of cytosine DNA methylation, and their relationship with heterosis in rice - K. Sakthivel; K. Girishkumar; G. Ramkumar; V. V. Shenoy; S. T. Kajjidoni; P. M. Salimath (Euphytica, 2010)

Petroleum Hydrocarbon Concentrations in Marine Sediments Along Chennai Coast, Bay of Bengal, India - R. Venkatachalapathy; S. Veerasingam; T. Ramkumar (Bulletin of Environmental Contamination and Toxicology, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Influence of spacing on growth and yield of sugarcane raised throughin vitro micropropagation - S. Raghu; S. Jayaram; S. Ramkumar; P. Prabakaran; V. Vekatesalu (Sugar Tech, 2006)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)